Local Politics’s Effect on Local E_Procurement: A Study in Three Indonesian Local Governments - Nurmandi, Achmad (Advances in Social Sciences Research Journal, 2017)
In some local governments of Indonesia, a bigger representation in local parliament means more political power in controlling their local budget. As a result, local procurement process is mostly affected by local politicians although procurement process is applied electronic procurement. In this study we compare three local governments in Indonesia by using meta analysis of previous study on electronic procurement. Quantitative and qualitative research method is used to investigate relationship between private sectors, politicians, and government officers. We found that e-procurement system applications in private/government firms has a positive effect on time efficiency. However, in three local government confirm that There is relationship between procurement information, completeness of information, information on evaluation, contract mechanism, and opportunistic behavior on e-procurement implementation. The local politicians, bureaucrats, and private companies have  organized and governed themselves to obtain benefit from “e-procurement” regulation. They did preparation from the budget planning until project procurement announcement in site.